2020
DOI: 10.7717/peerj.10023
|View full text |Cite
|
Sign up to set email alerts
|

Coral reefs as a source of climate-active aerosols

Abstract: We review the evidence for bio-regulation by coral reefs of local climate through stress-induced emissions of aerosol precursors, such as dimethylsulfide. This is an issue that goes to the core of the coral ecosystem’s ability to maintain homeostasis in the face of increasing climate change impacts and other anthropogenic pressures. We examine this through an analysis of data on aerosol emissions by corals of the Great Barrier Reef, Australia. We focus on the relationship with local stressors, such as surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 176 publications
(241 reference statements)
0
3
0
Order By: Relevance
“…Coral reefs have themselves been suggested to contribute to local ocean thermal regulation because many classes of unicellular marine algae, including those related to coral reefs, produce considerable amounts of dimethyl sulphide (DMS), a compound known to serve as cloud condensation nuclei and contribute to marine cloud formation (Jackson et al, 2020). A study on the GBR found that periods of low‐level cloudiness coincided with high local DMS flux, had a negative feedback on SSTs, and limited coral bleaching; conversely very low local DMS flux from bleached reef areas coincided with SST anomalies of up to 3°C (Jones et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Coral reefs have themselves been suggested to contribute to local ocean thermal regulation because many classes of unicellular marine algae, including those related to coral reefs, produce considerable amounts of dimethyl sulphide (DMS), a compound known to serve as cloud condensation nuclei and contribute to marine cloud formation (Jackson et al, 2020). A study on the GBR found that periods of low‐level cloudiness coincided with high local DMS flux, had a negative feedback on SSTs, and limited coral bleaching; conversely very low local DMS flux from bleached reef areas coincided with SST anomalies of up to 3°C (Jones et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Coral reefs provide key ecosystem services: biodiversity, coastal protection, biogeochemical cycling, fisheries, provision of raw materials, and cultural benefits (Woodhead et al, 2019). Recently, an ecosystem service of short-term regulation of regional climate has been suggested too, at least for the large extending Great Barrier Reef (Jones, 2015;Jackson et al, 2020). This climate effect would operate from the observed capacity of coral reefs to emit volatile sulfur in the form of dimethylsulfide (DMS).…”
Section: Introductionmentioning
confidence: 99%
“…In the atmosphere, emitted DMS oxidizes to form precursors of aerosols that enhance the formation, lifetime, and brightness of low-level clouds (Charlson et al, 1987;Simo, 2001), and thereby potentially reduce incident solar irradiance and temperature. Since the production and emission of DMS from coral reefs is triggered under higher irradiance and temperature, this reef-atmosphere interaction could potentially act as a regional thermostat (Jackson et al, 2020). This hypothesis is currently under scrutiny.…”
Section: Introductionmentioning
confidence: 99%